Respostas
respondido por:
8
O terno ordenado (k, 2, k + 1)
4x + 5y - 3z = 10.
(x, y, z)
(k, 2, k + 1)
sendo
x = k
y = 2
z = k + 1
SUBSTITUINDO em (x,y,z)
4x + 5y - 3z = 10
4(k) + 5(2) - 3(k + 1) = 10
4k + 10 - 3k - 3 =10
4k - 3k + 10 - 3 = 10
1k + 7 = 10
1k = 10 - 7
1k = 3
k = 3/1
\bigstar k = 3 \bigstar
4x + 5y - 3z = 10.
(x, y, z)
(k, 2, k + 1)
sendo
x = k
y = 2
z = k + 1
SUBSTITUINDO em (x,y,z)
4x + 5y - 3z = 10
4(k) + 5(2) - 3(k + 1) = 10
4k + 10 - 3k - 3 =10
4k - 3k + 10 - 3 = 10
1k + 7 = 10
1k = 10 - 7
1k = 3
k = 3/1
\bigstar k = 3 \bigstar
Gustavogg01:
oque é bigstar?
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás